Micromalteação e marcadores moleculares como suporte ao melhoramento de cevada cervejeira - Toniazzo, Claudia (2014)
The breeding to select more productive varieties with industrial quality adequate, resistant and tolerance to biotic and abiotic, respectively, and with better ecological adaptation stresses, helps to increase farm incomes. The case of the malting barley, improvement selects the best genotypes aiming at incorporating genes associated with quality malt. However, this method can narrow genetic variability, which can be critical when the selection is based solely on the phenotype examined by micromalteação. The use of molecular markers as an aid in identifying the diversity of genotypes, becomes a effective tool in breeding programs aimed at the beer market. In the same way enable the selection of characteristics difficult to be evaluated because directly access the polymorphism in the DNA level. The objective of this study was to analyze and determine the genetic distance among 12 genotypes belonging to the genetic improvement programme of barley at Embrapa Trigo, with the purpose to guide future crosses aimed at malt quality. To conduct the study, seeds of barley cultivated in 2012 were collected at three locations in Rio Grande do Sul and four locations on Paraná. Micromalting services were conducted at the Laboratory Versuchsund Lehranstaltfuer Brauerei (VLB, Germany) and InBev (United States). The variables were: index Kolbach, β-glucans, α-amylase and diastatic power. Molecular analysis was performed using 16 microsatellite markers specific for acevada in horizontal agarose electrophoresis gel and 3% and 4% system. The characteristics of micromalting of all genotypes were highly influenced by the environment to the different locations. BRS Brau, BRS Korbel showed the best values for malt quality, and Victor Graeff/RS was the site that showed the best environmental conditions for the expression of the variables. This study showed that in 2012 the Brazilian cultivars showed superior malt quality of international standard cultivar Scarlett. From the analysis with microsatellite and linking up the genotypic data with phenotypic markers, genotypes who have excelled in malt quality appeared in the same groups as the genetic diversity. However, when examining the relationship between genotypes and genetic diversity of the materials evaluated by microsatellite genetic distances was identified by the formation of more groups, when compared with the results just micromalting. Therefore, the use of molecular markers demonstrates greater specificity of data and can be immediately used in breeding programs of malting barley